Insights into customer experience in sports retail stores. Issue 2 (25th June 2020) - Happ, Elisabeth; Scholl-Grissemann, Ursula; Peters, Mike; Schnitzer, Martin
Abstract : Purpose: Offline retail stores have been working on improving their in-store customer experience; they have begun to realise the physical advantage they have over online channels. Especially sports products have a number of unique features, such as high emotional involvement or a sense of community; additionally, sports customers put emphasis on multisensory brand experience at the point of sale. This study examines the in-store customer experience (ISCX) in offline sports retail stores, taking into account the commercial uniqueness of sport. Design/methodology/approach: A qualitative study (focus groups; n = 16) and quantitative survey (cross-sectional survey design; n = 238) were conducted to measure ISCX in sports retail stores. Findings: The results suggest that the customers' in-store experience has a significant influence on customers' satisfaction with the sports retailer and their likeliness to recommend the store to friends, which, in turn, is significantly affected by customers' satisfaction with the retailer. Moreover, social responses to actors involved in the service encounter, for example, the interaction with employees, play a significant role for the customer in-store experience. Accordingly, sports customers strive not only for functional benefits inherent in the interaction with customers and employees but also for social benefits. Originality/value: This study extends the knowledge by (1) replicating the ISCX scale, (2) analysing ISCX in a sports retail environment and (3) examining the influence of ISCX on the Net Promoter Score. Moreover, the findings support managers' know-how about in-store setting and help to maintain the customer relationship.